Pathologic fracture healing after femoral limb salvage in a dog. Issue 3 (3rd December 2019) - Hayes, MA; Jemilo, S; Muir, P; Sullivan, R; Bleedorn, JA
Abstract : Background: Bone sarcomas are a significant cause of pain, disability, and mortality in dogs. A variety of surgical limb salvage options are available to preserve limb function with comparable prognosis to amputation. Case Report: This report describes successful healing after plate fixation of an undifferentiated sarcoma pathologic femoral fracture in a dog. The fracture was treated surgically with curettage of the tumour site, placement of autogenous bone graft, and then stabilized using a locking plate rod construct. The patient regained excellent mobility after surgery and was managed with monthly pamidronate therapy. Serial radiographs demonstrate progressive healing of the pathologic fracture. Ultimately, the patient developed a maxillary fibrosarcoma and was euthanased 1 year after treatment of the femoral fracture. Postmortem histopathological evaluation of the pathologic fracture site demonstrated complete bone healing. Conclusion: This case highlights the possibilities of limb salvage by fracture stabilization and bone healing as a viable option in select patients.